Dual-task functional exercises as an effective way to improve dynamic balance in persons with intellectual disability – continuation of the project - Mikołajczyk, Edyta; Jankowicz-Szymańska, Agnieszka (Medical Studies/Studia Medyczne, 2017)
Introduction: Balance disorders are common in people with intellectual disability (ID). Aim of the research: The continuation of the project is aimed at finding out whether extension of the unstable surface dual-task functional exercises programme by another 12 weeks affects the level of dynamic balance in adolescents with ID and what those changes are like after the 8-week summer holidays. Material and methods: A total of 17 adolescents with ID aged 14–16 years (E) performed functional exercises for another 12 weeks on unstable surfaces, and a group of 17 individuals with ID were the controls. Dynamic balance was assessed three times: after the first stage of the programme (test 2), after another 12 weeks (test 3), after the 8-week holiday (test 4). ALFA AC An International East stabilometric platform was used for measurements. Results : No statistical differences were discovered in group E, in dynamic balance assessment between test 2 and 3; however, the mean scores in group E, in test 3, were slightly better than in test 2, and notably better than in group C. No significant differences between test 3 and 4 were found in group E either. Conclusions : Extension of the intervention program helped to maintain improved dynamic balance. Discontinuation of the program for the period of 8 weeks resulted in decreased level of balance; however, it was still higher than at the beginning of the project. Dual-task functional exercises based on activities of daily living (ADLs) and stimulation of righting reactions may enhance dynamic balance in individuals with ID, but it should be constantly stimulated.